Quality Attributes of Fresh-Cut Coconut after Supercritical Carbon Dioxide Pasteurization - Giovanna Ferrentino; Ana Belscak-Cvitanovic; Drazenka Komes; Sara Spilimbergo (Journal of Chemistry)
The impact of supercritical CO2 (SC-CO2) process on the quality attributes of fresh-cut coconut has been investigated to establish the acceptability of SC-CO2 treated products by the consumers. Two process conditions, previously identified as optimal to reduce the microbial content of the product, were studied: 12 MPa, 40°C, 30 min and 12 MPa, 45°C, 15 min. The results highlighted that both conditions induced some effects on product attributes. After 30 min of treatment at 12 MPa and 40°C a decrease of lightness (8%), pH (13%), fat content (24%), total phenol content (29%), flavonoid compounds (49%), antioxidant capacity (30%) and an increase of dry matter (11%) and titratable acidity (51.1%) were observed while polyphenol oxidase (PPO) exhibited 35% and 98.5% inactivation. Peroxidase enzyme activity increased by 77.8% and 30.4% at 12 MPa, 40°C, 30 min and 12 MPa, 45°C, 15 min, respectively. Sensory evaluations revealed no significant differences in appearance, texture, taste, and aroma of treated fresh-cut coconut compared to the untreated. The study confirms the feasibility of SC-CO2 process for the pasteurization of fresh fruits with a firm structure and opens the door to the possibility of exploiting such a technology at industrial level.